Immune evasion of Borrelia burgdorferi by acquisition of human complement regulators FHL-1/reconectin and Factor H - Kraiczy, Peter; Skerka, Christine; Kirschfink, Michael; Brade, Volker; Zipfel, Peter F. (European journal of immunology, 2001)
To understand immune evasion mechanisms of Borrelia burgdorferi we compared serum-resistant B. afzelii and serum-sensitive B. garinii isolates for their capacity toacquire human complement regulators. Here we demonstrate that the two borrelial genospecies show different binding of the two important human complement regulators, FHL-1/reconectin and Factor H. All serum-resistant B. afzelii isolates bound FHL-1/reconectin and also Factor H, and all analyzed serum-sensitive B. garinii isolates showed no or a significantly lower binding activity. Using recombinant deletion mutants, the binding domains were localized to the C terminus of FHL-1/reconectin to short consensus repeats 5-7. The borrelial binding proteins were located in the surface of the bacteria as demonstrated by immunofluorescence staining of intact, serum-exposed bacteria and by enrichment of outer membrane proteins. The surface-attached complement regulators maintained complement regulatory activity as demonstrated in a cofactor assay. By ligand blotting two different borrelial binding proteins were identified that were responsible for the surface attachment of FHL-1/reconectin and Factor H. These borrelial complement regulators acquiring surface proteins (CRASP) were further characterized as either CRASP-1, a 27.5-kDa molecule which preferentially binds FHL-1/reconectin and which was present in all serum-resistant borreliae, or CRASP-2, a 20/21-kDa protein which interacts preferentially with Factor H and the expression of which was more restricted, being detected in four of the six isolates analyzed. In summary, we describe a new immune evasion mechanism of B. burgdorferi, as these bacteria acquire human complement regulators to control complement activation on their surface and to prevent formation of toxic activation products.